Conditioning effect of transcranial magnetic stimulation evoking motor‐evoked potential on V‐wave response. Issue 12 (11th December 2014) - Grosprêtre, Sidney; Martin, Alain
Abstract The aim of this study was to examine the collision responsible for the volitional V‐wave evoked by supramaximal electrical stimulation of the motor nerve during voluntary contraction. V‐wave was conditioned by transcranial magnetic stimulation (TMS) over the motor cortex at several inter‐stimuli intervals (ISI) during weak voluntary plantar flexions (n = 10) and at rest for flexor carpi radialis muscle (FCR; n = 6). Conditioning stimulations were induced by TMS with intensity eliciting maximal motor‐evoked potential (MEPmax). ISIs used were ranging from −20 to +20 msec depending on muscles tested. The results showed that, for triceps surae muscles, conditioning TMS increased the V‐wave amplitude (~ +250%) and the associated mechanical response (~ +30%) during weak voluntary plantar flexion (10% of the maximal voluntary contraction ‐MVC) for ISIs ranging from +6 to +18 msec. Similar effect was observed at rest for the FCR with ISI ranging from +6 to +12 msec. When the level of force was increased from 10 to 50% MVC or the conditioning TMS intensity was reduced to elicit responses of 50% of MEPmax, a significant decrease in the conditioned V‐wave amplitude was observed for the triceps surae muscles, linearly correlated to the changes in MEP amplitude. The slope of this correlation, as well as the electro‐mechanical efficiency, was closed to the identity line, indicating that V‐wave impact at muscle level seems to be similar to the impact of cortical stimulation. All these results suggest that change in V‐wave amplitude is a great index to reflect changes in cortical neural drive addressed to spinal motoneurons.